The Diagnostic Value of High-Frequency Ultrasound in Unclarified Lesions at the End of Extremities - Haojie Yang; Na Ni; Weiwei Ren; Qiao Wang; Mengyu Lu; Yincheng Gao; Guanqun Zhang; Yongxian Lai; Yujing Zhao; Lehang Guo; Dandan Shan; Liping Sun (Diagnostics, 2025)
Objectives: Unlike other body parts, unclarified lesions at the end of extremities have unique challenges due to their small size and interference. Traditional imaging methods struggle with low resolution. HFUS enhances resolution, offering a potential diagnostic value. Methods: From January 2019 to October 2023, the clinical and HFUS data of patients with unclarified lesions at the end of extremities were retrospectively analyzed. Independently, the diagnosis was made using two diagnostic modes (Mode A: only clinical information; Mode B: clinical and HFUS information). The diagnostic performance of the two modes was evaluated across different classification methods. Results: For all lesions, the correct rate of Mode B was higher than that of Mode A (52.8% vs. 18.4%, p < 0.001), and the indeterminate rate decreased by 43.0%. For benign lesions (51.0% vs. 18.2%), subungual lesions (40.8% vs. 21.1%), non-subungual lesions (55.6% vs. 17.8%), and common cases (60.9% vs. 20.3%), the diagnostic correct rate of Mode B was also higher than that of Mode A (all p < 0.05). However, there was no significant difference in rare lesions (9.8% vs. 4.9%) and malignant lesions (62.9% vs. 19.4%) between the two modes (both p > 0.05). Moreover, the indeterminate rate for all categories of lesions significantly diminished. Otherwise, Mode B demonstrated strong performance for malignant lesions (85.7% vs. 42.9%, p < 0.001). Conclusions: Adding HFUS can significantly improve the accuracy of diagnosing unclarified lesions at the end of extremities and reduce uncertainty, especially for benign and common lesions. HFUS has also demonstrated better performance in screening for malignant lesions.